2017
DOI: 10.3390/socsci6030097
|View full text |Cite
|
Sign up to set email alerts
|

Mattering Moralities: Learning Corporeal Modesty through Muslim Diasporic Clothing Practices

Abstract: Questions of 'coveredness' in Islamic codes of dress, particularly as they apply to women, are often framed through the symbolic statements that they enable or disable, or through discourses on public versus private spaces. Rather than focus on these disciplining dimensions, this article explores observations about embodied practices for clothing oneself 'modestly', and some of the paradoxes thereof, which emerged in the context of research about diasporic mobilities of European-Moroccans in Morocco. Drawing h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Eventually, they would become analytically instrumental to Lauren in approaching participants' claims about their sense of embodiment and how their sense of unbelonging in Morocco can take sensory, corporeal forms through how a body feels in the clothes it is wearing. 42 Having attuned her own body to similar clothing in the process of doing ethnography, she found that she could recognise the corporealities her participants described as visceral experiences herself.…”
Section: Unplanned Experiment: Discovering Thresholdsmentioning
confidence: 99%
“…Eventually, they would become analytically instrumental to Lauren in approaching participants' claims about their sense of embodiment and how their sense of unbelonging in Morocco can take sensory, corporeal forms through how a body feels in the clothes it is wearing. 42 Having attuned her own body to similar clothing in the process of doing ethnography, she found that she could recognise the corporealities her participants described as visceral experiences herself.…”
Section: Unplanned Experiment: Discovering Thresholdsmentioning
confidence: 99%
“…Shanneik enhances Nora's concept by bringing in the transnational as the field of identity-making. The third article of this section, Mattering Moralities: Learning Corporeal Modesty through Muslim Diasporic Clothing Practices by Lauren B. Wagner, examines how gendered Muslim corporeality (through clothing practices) is negotiated in a transnational field by constantly physically mobile European-Moroccans (Wagner 2017). The author researches how moral bodies materialize with and through clothing by observing and following the constant mobilities of social actors who are moving back and forth across spaces dominated by "Muslim" and "Western" "regimes of modesty and morality," as Wagner puts it.…”
Section: Contributions In This Issuementioning
confidence: 99%